Pelatihan Origami Bagi Anak Usia Dini di Paud Jannatul Na’iem Sungai Buluh - Lady Diana Yusri; Adrianis Adrianis; Aulia Rahman; Darni Enzimar Putri; Dini Maulia; Idrus Idrus; Imelda Indah Lestari; Rachmidian Rahayu; Radhia Elita; Rahtu Nila Sepni; Rima Devi; Rina Yuniastuti (Warta Pengabdian Andalas, 2019)
Origami is one of the arts in folding paper from Japan. Through this origami workshop, not only adults, even the children, could increase their imagination and creativity in the early years. Based on this reason, Japanese Department Universitas Andalas carried out the Origami workshop to the children in the PAUD Jannatul Nai'em Sungai Buluh. This workshop was a part of community service as the lecturer of the University. The workshop activity provided three sessions. The first session was to give an introduction about origami for understanding, history, types, and benefits of origami. The second session was training on making origami in various forms. Then the last session was evaluation, which aims to confirm whether the children could absorb the material well and whether the children could work on the process of making origami on their own. This activity was very beneficial for children in improving their motoric skills. Origami is an alternative skill game where the skill games begin to abandon due to the presence of a smartphone and other digital gadgets.